2018
DOI: 10.1111/his.13449
|View full text |Cite
|
Sign up to set email alerts
|

Primary effusion lymphoma in Taiwan shows two distinctive clinicopathological subtypes with rare human immunodeficiency virus association

Abstract: Apart from the phenotypical difference, our HHV8-positive neoplasms were not distinct from the HHV8-negative group. Literature review of 256 cases, including our cases, revealed that HHV8-positive cases were associated more frequently with HIV and EBV infection, with rare MYC rearrangement, and a poorer prognosis than HHV8-negative cases. We propose to name the HHV8-positive cases as 'classical' or 'type I PEL' and the HHV8-negative cases as 'type II PEL', stressing the similarities and the distinctive feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 40 publications
4
37
1
Order By: Relevance
“…Their phenotype was determined to be either of B‐cell or plasmablastic. Based on the HHV8 status, the HHV8‐positive cases were considered to be typical (or type I) PEL as defined in the WHO classification scheme, while those negative for HHV8 were designated as type II PEL according to our previous study on effusion lymphomas 16 . Those with secondary effusion involvement was defined as cases with prior, synchronous, or metachronous involvement by nodal, soft tissue, or marrow‐based hematopoietic malignancies of the same type.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their phenotype was determined to be either of B‐cell or plasmablastic. Based on the HHV8 status, the HHV8‐positive cases were considered to be typical (or type I) PEL as defined in the WHO classification scheme, while those negative for HHV8 were designated as type II PEL according to our previous study on effusion lymphomas 16 . Those with secondary effusion involvement was defined as cases with prior, synchronous, or metachronous involvement by nodal, soft tissue, or marrow‐based hematopoietic malignancies of the same type.…”
Section: Methodsmentioning
confidence: 99%
“…Cases no. 1, 2, 4, and 7 were included in our previous study of PEL in Taiwan 16 . All these patients presented with massive PE and none of them was associated with HIV infection, immunosuppression from organ transplant, medications for autoimmune diseases, hepatitis B virus infection, cirrhosis, pyothorax, or chronic inflammation.…”
Section: Clinicocytological Features Of Patients With Pelsmentioning
confidence: 99%
“…that distinguish it from PEL 33. In our recent study of PEL in Taiwan with a literature review of 256 cases, we identified a group of patients with HHV8-negative EBL and with rare HIV infection, in contrast to the HIV-and HHV8-double positive classical PEL in the WHO classification 34. Interestingly from our current study, there might be a small number of PEL or EBL comprising of ENKTL.…”
mentioning
confidence: 55%
“…rare cases of primary effusion lymphoma might resolve after pleurocentesis without chemotherapy. 6,7 Improvements in the understanding and diagnosis of CML are considered one of the most successful cancer medicine stories of the past century. 2 Instead of cytoreduction chemotherapy in the past, nowadays TKI is the standard treatment modality for CML.…”
Section: Discussionmentioning
confidence: 99%